Effect of Vetiveria zizanioides on experimentally induced dyslipidemia - SANGEETHA RAJA; JAMUNA RANI; SATYAJIT MOHAPATRA; ALWIN D (International Journal of Pharma and Bio Sciences, 2017)
To evaluate the hypolipidemic effect of Vetiveria zizanioides Oil in High Fat Diet (HFD) induced Wistar Albino rat model. They were divided into five groups of six animals each as Normal Diet Control, High Fat Diet Control, with Low dose Vetiver Oil (VO), with High dose VO, with Simvastatin (Group I-V respectively) for 8 weeks, along with the VO emulsion and Simvastatin orally once daily. Weight of the animals was measured every week and the lipid parameter Total cholesterol, Triglycerides, High Density Lipoprotein, Low Density Lipoprotein were estimated at baseline, 4th week and 8th week. HFD significantly increased plasma lipid levels and weight. Decrease in plasma lipids except HDL, were observed in experimental drug and Simvastain treated group. Raise in HDL and decrease in weight gain observed in Group III, IV and V when compared to Group II. Vetiveria zizanioides demonstrated hypolipidemic activity in HFD induced rats might be due to its underlying antioxidant effect.